KUALITAS HIDUP ANAK DENGAN ASMA DI RSUD DR. SOEKARDJO KOTA TASIKMALAYA DAN RSUD KABUPATEN CIAMIS - Hani Handayani; Asep Setiawan (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2019)
Asthma is a disease that can cause morbidity and mortality in children. The incidence, severity lavel of disease associated with asthma has increased. The prevalence in the world is estimated of 10% occured in children. The prevalence in Regional public hospitals of dr. Soekardjo Tasikmalaya is estimated of 5% whereas in Regional Public hospital Ciamis is estimated of 20%. Asthma in children is a problem for patients and families, because it affects the various specific aspects related to the quality of life. This research aims to know the quality of life of children with asthma in Regional Public Hospital of dr. Soekardjo Tasikmalaya and Ciamis. This research is analytic descriptive research. The sample in this research were children aged 7-18 years with asthma who visited the outpatient service with a total of 72 respondents with consecutive sampling techniques. The Generic version of the PedsQl 4.0 Core Scale is used to measure quality of life. Data analysis univariate analysis is used by using a frequency distribution. The results showed that most of respondents have a quality of life that is at risk as much as 59 people (81.9%). Based on the results, it recommended for more information and education by health professional personnel to patients and their families about prevention and management of asthma. Keywords: Asthma, Quality of life of children